Limits to arbitrage in markets with stochastic settlement latency - Nikolaus Hautsch; Christoph Scheuch; Stefan Voigt (Goethe University Frankfurt, Center for Financial Studies (CFS), 2018)
Distributed ledger technologies rely on consensus protocols confronting traders with random waiting times until the transfer of ownership is accomplished. This time consuming settlement process exposes arbitrageurs to price risk and imposes limits to arbitrage. We derive theoretical arbitrage boundaries under general assumptions and show that they increase with expected latency, latency uncertainty, spot volatility, and risk aversion. Using high-frequency data from the Bitcoin network, we estimate arbitrage boundaries due to settlement latency of on average 124 basis points, covering 88% of the observed cross-exchange price differences. Settlement through decentralized systems thus induces non-trivial frictions affecting market efficiency and price formation.
urn:nbn:de:hebis:30:3-480536
Keywords: G00; G10; G14; 330; Arbitrage; Settlement Latency; Distributed Ledger; Blockchain